Referrals to palliative care for cardiovascular patients: a 10-year longitudinal retrospective study. (3rd October 2022) - Ecarnot, F; Giffard, M; Seydou Sall, F; Van Bulck, L; Becoulet, N; Seronde, M F
Abstract: Background: Patients with cardiovascular diseases have a significant symptom burden and often have a progressive course towards end-stage disease and ultimately, death. For this reason, consensus guidelines advocate early integration of palliative care into the care for cardiovascular patients, especially those with heart failure. However, palliative care involvement in the care of cardiovascular patients remains suboptimal, whereby only a small proportion of patients are referred to palliative care specialists, and often too late in the disease course. We aimed to examine the current situation and describe the profile, circumstances of death, and time of referral to palliative care of cardiovascular patients over a 10 year period in our unit. Methods: This retrospective study included all patients with cardiovascular disease who were referred to the mobile palliative care team by the cardiology unit, in a single, large University Hospital in France between 2010 and 2020. All data were extracted from the medical hospital files. We recorded vital status, day of birth, time of referral to palliative care, day of death, and medical diagnoses. We noted whether patients had advance directives (AD). Results: A total of 148 patients were identified; full data were available for 144 (97.3%). Of these, 136 (94.4%) died, while 8 (5.6%) were still alive in March 2022. The mean age at the time of death was 75±14 years. The median time between referral to palliative care and death was 9 days (interquartiles, 2, 41.5). We noted the following underlying diseases (patients could have more than one diagnosis): 111 (77%) had heart failure, 58 (40.2%) had ischemic heart disease, 55 (38.2%) had valvular heart disease, 39 (27%) had diabetes, 37 (25.7%) had chronic kidney disease, 30 (20.8%) had pulmonary hypertension, 17 (11.8%) had chronic obstructive pulmonary disease. In addition, 78 (54%) had at least one documented episode of atrial fibrillation, 27 (18.7%) had had a stroke. Place of death was available for 119 patients (82.6%) (Figure): The majority (73, 61.4%) died in the Cardiology department of our hospital; only 17 (14.3%) died at home (see Figure 1). Only 4 patients (2.7%) had documented AD. Conclusion: This study suggests that palliative care is still widely under-used in cardiology patients, and is often initiated very close to the time of death, and mainly for heart failure patients. A large proportion of patients still die in the hospital setting. Further, prospective studies are warranted to investigate whether these dispositions corresponds to patients' wishes, and whether earlier initiation of palliative care could improve quality of life for cardiology patients with end-stage disease. Funding Acknowledgement: Type of funding sources: None.